Independent and combined associations of high-density lipoprotein cholesterol-modified triglyceride-glucose index with all-cause and cardiovascular mortality in patients with acute decompensated heart failure - He, Shiming; Xie, Lin; Xie, Guobo; Jian, Guoan; Jiang, Kun; Lu, Zihao; Zhang, Shuhua; Wang, Qun; Lu, Hengcheng; Xiong, Zhiyu; Wu, Zhiting; Sheng, Guotai; et al. (Frontiers in Endocrinology, 2025)
IntroductionDysregulation of glucolipid metabolism is a central pathological mechanism underlying acute decompensated heart failure (ADHF) and significantly impacts its poor prognosis. This study aims to investigate the association between the high-density lipoprotein cholesterol-modified triglyceride-glucose index (defined as TyG/HDL-C) and their interaction with 30-day mortality in patients with ADHF.MethodsFrom 2018 to 2024, 2,329 ADHF patients enrolled in the Jiangxi-ADHF II cohort were included. Multivariable Cox regression models were utilized to evaluate the association between TyG/HDL-C ratio and 30-day all-cause/cardiovascular mortality risk. A 3-dimensional interaction model was employed to examine the dose-response relationships of TyG and HDL-C with mortality risk. Additionally, exploratory mediation models were constructed to investigate potential mediating effects of inflammation, oxidative stress, and nutritional metabolism in the association between TyG/HDL-C ratio and mortality risk.ResultsAt 30-day follow-up, 150 deaths occurred, 115 of which were cardiovascular. Multivariable Cox regression showed that each standard deviation increase in TyG/HDL-C ratio increased 30-day all-cause mortality by 24% and cardiovascular mortality by 20%. These findings demonstrated robustness across sensitivity analyses conducted from four dimensions: model adjustment, causal timing, population heterogeneity, and data integrity. Notably, the subsequent 3-dimensional interaction model analysis revealed a complex U-shaped association — resembling a concave surface of a radio telescope — between the combined effects of TyG index and HDL-C on mortality risk. Specifically, both excessively low and high combinations of TyG index and HDL-C were associated with elevated 30-day mortality risk in ADHF patients, while the lowest mortality risk interval occurred when the TyG index remained within 7.5–9.0 and HDL-C levels were maintained at 1.0–1.5 mmol/L. Mediation analysis further suggested that inflammatory and nutritional pathways might serve as significant mediators of mortality risk related to TyG/HDL-C ratio.DiscussionThe TyG/HDL-C ratio emerged as an independent predictor of short-term all-cause and cardiovascular mortality in ADHF patients, demonstrating significant enhancement in predictive performance for these outcomes. Most notably, the concave-shaped interaction pattern revealed by 3-dimensional interaction analysis provided an evidence-based threshold framework for metabolic management in ADHF patients, which may hold substantial clinical significance for reducing future mortality risks in this population.